(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Batik is one of the nation’s great cultural heritage. Each region also has batik art. The city of Surabaya also has a unique batik culture, one of which is Semanggi batik. It is hoped that the batik business will encourage opportunities for people’s economic strength and competitiveness. But in fact, the competitiveness of Semanggi batik products is low. This study aims to identify the strengths and weaknesses (internal environmental conditions) and to identify opportunities and threats (external conditions) of the semanggi batik craftsmen group as the basis for formulating strategies to improve competitiveness. The study used a qualitative approach with data collection techniques, focus group discussion (FGD), semi-structured interviews, observation, and document collection. Informants are determined using purposive. The data analysis uses interactive models and SWOT analysis. The results showed that the internal conditions that support the floating strength of semanggi batik include distinctive iconic motifs that distinguish them from other batik and batik coloring using organic materials. Opportunities that arise are export opportunities, city government support, support from other elements of society, and online marketing opportunities. While the existing weaknesses include the number of artisans, low digital-based marketing capabilities, batik motifs that have not been registered as intellectual property rights, limited production, and marketing volume, low capital. The threats that arise are the emergence of competitors and expensive production costs that affect the selling price of batik. The map of the internal and external conditions of the semanggi batik craftsmen is handy as a material for formulating strategy formulations in empowering semanggi batik artisans